OBSERVATIONS AND INTERPRETATION OF THE PHOTOMETRIC VARIABILITY OF TT ARI - Suleimanov, V. F.; Zhukov, G. V.; Senio, D. S. (Одеські астрономічні публікації, 2017)
Simultaneous WBVR photometric observations of TT Ari during 94 / 95 years are presented. The periodogram analysis of the obtained light curves and colours are curried out. The photometric period equal 3.2 h and its one day aliases are found from light curves, but the period equal spectroscopic (3.3 h) are found from B-V colours in the observations, performed in 1994. The quasi-periodic oscillations (QPO) with period from 47 to 16 minutes, changing from night to night are found too. A new model of the tilted precessing accretion disk together with reflection from secondary or hot spot is suggested to explanation of the photometric variability of TT Ari. It is proposed that QPO is possibly connected with orbiting blobs in the accretion disk.